2018
DOI: 10.7554/elife.31807
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific glycosylation regulates the form and function of the intermediate filament cytoskeleton

Abstract: Intermediate filaments (IF) are a major component of the metazoan cytoskeleton and are essential for normal cell morphology, motility, and signal transduction. Dysregulation of IFs causes a wide range of human diseases, including skin disorders, cardiomyopathies, lipodystrophy, and neuropathy. Despite this pathophysiological significance, how cells regulate IF structure, dynamics, and function remains poorly understood. Here, we show that site-specific modification of the prototypical IF protein vimentin with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 131 publications
(263 reference statements)
5
79
0
Order By: Relevance
“…2a). We anticipate that the ability to couple force measurements with highresolution, volumetric optical imaging will be a powerful tool for studying the mechanobiology and regulation of the IF cytoskeleton, which remain poorly understood 27,37 . For example, vimentin filaments organize around the nucleus (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2a). We anticipate that the ability to couple force measurements with highresolution, volumetric optical imaging will be a powerful tool for studying the mechanobiology and regulation of the IF cytoskeleton, which remain poorly understood 27,37 . For example, vimentin filaments organize around the nucleus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also set the stage for new discoveries on IF cytoskeleton regulation. All IF proteins are decorated with post-translational modifications (PTMs), including phosphorylation and O-glycosylation, which may alter IF function 37,40 . We previously demonstrated that the site-specific O-glycosylation of vimentin is required for IF assembly and function in human cells 37 , but the real-time effects of these PTMs on IF network dynamics and mechanical properties remain elusive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our observation that silencing GFPT expression increases bacterial 403 diameter strongly supports the hypothesis that UDP-GlcNAc, or an intermediate along the 404 HBP, is hijacked into the inclusion to fuel bacterial division, possibly by feeding peptidoglycan 405 synthesis. One recent publication showed that UDP-GlcNAc is also used during infection to 406 post-translationally modify the intermediate filament vimentin and this also could contribute 407 to significant UDP-GlcNAc consumption in C. trachomatis infection(Tarbet, Dolat et al, 2018). 408…”
mentioning
confidence: 99%